The Patagonian intraplate basalts: A reflection of the South Atlantic convection cell - Soager, Nina; Holm, Paul Martin; Massaferro, Gabriela Isabel; Haller, Miguel Jorge F.; Traum, Marie Katrine (Gondwana Research)
Based on an extensive literature dataset on Cenozoic intraplate basalts from Patagonia, Argentina, we provide a revised interpretation of the mantle sources of volcanism and suggest a relation to the South Atlantic hotspots and mantle flow. Furthermore, we present 16 elemental analyses of North Patagonian basalts as well as 12 Sr, Nd and Pb-isotopes. The new data reveal that the North Patagonian basanite-nephelinite rocks with HIMU OIB-type trace element patterns do not have highly radiogenic Pb-isotopes and are unrelated to the South Patagonian HIMU-type Pali Aike source. Instead, they were formed within the lifetime of the South Atlantic Ocean by metasomatism of the local lithospheric mantle (SCLM) by carbonatitic melts from the ambient South Atlantic asthenosphere. Thus, they are an example of a very young HIMU source supporting that the HIMU OIB-type signature was formed by carbonate metasomatism of lithospheric mantle and not by recycling of oceanic crust. In contrast, the EM1-type basalts dominating in Central Patagonia have significantly elevated FeOT/MnO (up to 79) and low CaO contents (mostly between 8 and 9 wt%). This indicates derivation from a pyroxenitic source, which presumably formed by melt metasomatism of the SCLM. In isotopic space, the Patagonian basalts can be modelled by mixing of depleted South Atlantic MORB mantle (representing the SCLM) with 2–7% Discovery and Bouvet hotspot melts in varying proportions (representing the metasomatizing agents). The latitudinal variation in isotopic compositions of the Patagonian basalts is a mirror image of the variation at the mid-Atlantic Ridge. This observation is consistent with the westward direction of the mantle flow and drift of South America and suggests that the hotspot locations and flow direction of the South Atlantic convection cell has been stable for a significant part of the lifetime of the South Atlantic ocean bringing plume influenced asthenosphere westwards beneath Patagonia. Fil: Soager, Nina. Universidad de Copenhagen; Dinamarca ...